2009
DOI: 10.1021/jp901184t
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution STM Studies of Terephthalic Acid Molecules on Rutile TiO2(110)-(1 × 1) Surfaces

Abstract: The structure of terephthalic acid (TPA) molecules adsorbed on rutile TiO 2 (110)-(1 × 1) has been investigated by scanning tunneling microscopy (STM). Molecularly resolved STM images show formation of monolayer with the tendency of TPA molecules to form dimer rows along the [001] substrate direction. The ability to image functional groups by the STM tip, and single molecule diffusion are demonstrated. The quality and stability of the monolayer are tested, including the resistance against air exposure. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 33 publications
5
53
1
Order By: Relevance
“…Recently, combined STM and DFT calculations [14][15][16] suggested that at saturation coverage, TPA molecules undergo dimerization on TiO 2 (110) via attractive intermolecular interactions within the monolayer. The TPA dimers prefer to adopt a plane-to-plane configuration with a C 2 local symmetry, where the BTA dimer is stabilized by the formation of double hydrogen bonds between the hydroxyl and carbonyl oxygen of both apical carboxylic groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, combined STM and DFT calculations [14][15][16] suggested that at saturation coverage, TPA molecules undergo dimerization on TiO 2 (110) via attractive intermolecular interactions within the monolayer. The TPA dimers prefer to adopt a plane-to-plane configuration with a C 2 local symmetry, where the BTA dimer is stabilized by the formation of double hydrogen bonds between the hydroxyl and carbonyl oxygen of both apical carboxylic groups.…”
Section: Discussionmentioning
confidence: 99%
“…the occurrence of mono-and bidentate species) and into the question whether dimers of BA and TPA adsorbate species are present on TiO 2 (110). This question is particularly interesting in case of TPA, since for an upright species (as proposed in previous works [13][14][15][16]), one would assume the occurrence of both protonated and deprotonated carboxylic acid groups.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Here we stress that discussed changes in the appearance of molecules do not involve tip apex modifications. [37,38] …”
Section: Tip-induced Lateral Manipulation Of Vl Molecules On the Tio mentioning
confidence: 99%